Synthesis of gold and silver nanoparticles using Phlogacanthus Thyrsiformis extracts-its phytochemical screening and anti-oxidant studies - Singh, Avinash Thounaojam; Shaikh, Iqbal N.; Rale, Madhura Vijay (Materials Today-Proceedings, 2021)
Phlogacanthus Thyrsiformis is a shrub belonging to the Acanthaceae family, normally found in the northeastern parts of India, Nepal, Burma, Indo-Chinese region and Indonesia. It is used as a cure for diarrhoea, dysentery, cholera, burns, boils, high blood pressure, sprains and body pains. Silver and gold nanoparticles were synthesized from the extracts of the leaves of this plant as the some biomolecules, known as secondary metabolites, present in plant extracts can be used to reduce metal ions to nanoparticles. The contents of the leaves were extracted in various solvents and the tests for the presence of secondary metabolites were carried out. The gold and silver nanoparticles synthesized using the plant extracts and characterized using TEM, SEM techniques and the phytochemical screening tests were done for different extracts. The anti-oxidant studies of the several extracts were carried out. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Anti-oxidant studies; Nanoparticles; Phligacanthus thyrsiformis; Phytochemical Studies; Secondary metabolites